HUBUNGAN ANTARA PENGETAHUAN DAN PERILAKU SEKSUAL PRANIKAH DENGAN USIA PERNIKAHAN DINI DI KECAMATAN BOROBUDUR KABUPATEN MAGELANG - Rukma Tri Indriarti; Sri Wahyuni S; Titi Mursiti (Midwifery Care Journal, 2022)
Early marriage is a marriage performed by a male and female couple at the age of puberty (10-19 years). Data from the Ministry of  Religion of Magelang Regency from January to September 2020,  1069 marriages were married at the age of 16-21 years and as many as 154 married at the age of <16 years. While the data obtained at the Religious Affairs Office of the Borobudur District, the number of early marriages in 2020 was 11 teenagers and 3 teenagers January to February 2021. The factors that influence early marriage are knowledge, premarital sexual behavior, economy, family and community cultural traditions. The purpose of this study was to determine the relationship between knowledge and premarital sexual behavior with early marriage age in Borobudur District Magelang Regency. This research is a quantitative research type of analytic observational research with a cross-sectional approach. The number of samples is all adolescents aged less than 19 years who have married a number of 40 respondents. The sampling technique used was total sampling. The research instrument used a questionnaire sheet. Data analysis used Spearman Rank correlation test. The results showed that the variable related to early marriage age was knowledge (p value = 0.346), and the variable that was not related to early marriage age was premarital sexual behavior (p value = -0.211). From the results of the study, it is hoped that it can provide information and public understanding about premarital sexual knowledge and behavior, so as to prevent the occurrence of early marriage in adolescents